ANALISIS PENGALAMAN PENGGUNA PADA APLIKASI SISKA UNIVERSITAS BINA DARMA DENGAN MENGGUNAKAN USER EXPERIENCE QEUSTIONNAIRE (UEQ) - Firnando, Muhammad Iksan; Sutabri, Tata Sutabri (Infotech: Journal of Technology Information, 2025)
The study of this study is to evaluate the user experience of the Siska application used at Bina Darma University by utilizing the User Experience Questionnaire (UEQ) instrument.. Given the rapid development of information technology, the Siska application is expected to enhance efficiency and effectiveness in academic data management. This research involves active students as respondents, measured through six UEQ aspects: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The analysis results show that more than 80% of students are satisfied with the Siska application, reflecting its good performance in meeting user expectations. However, some aspects still require improvement, particularly in terms of clarity and ease of use. This study recommends enhancing application features and providing regular user education to support better understanding. Thus, the Siska application can continue to evolve to meet user needs and improve the quality of academic services at Bina Darma University.